The immunological phenotype of rituximab-sensitive chronic graft-versus-host disease: a phase II study - Suzanne van Dorp; Henrike Resemann; Liane te Boome; Floor Pietersma; Debbie van Baarle; Frits Gmelig-Meyling; Roel de Weger; Eefke Petersen; Monique Minnema; Henk Lokhorst; Saskia Ebeling; Scott J.P. Beijn; et al. (Haematologica, 2011)
Chronic graft-versus-host disease is the major long-term complication after allogeneic stem cell transplantation with a suboptimal response rate to current treatments. Therefore, clinical efficacy and changes in lymphocyte subsets before and after rituximab treatment were evaluated in a prospective phase II study in patients with steroid-refractory chronic graft-versus-host disease. Overall response rate was 61%. Only responding patients were found to have increased B-cell numbers prior to treatment. B cells had a naïve-antigen-presenting phenotype and were mainly CD5 negative or had a low CD5 expression. Normal B-cell homeostasis was reestablished in responding patients one year after ritxumab treatment and associated with a significant decline in skin-infiltrating CD8+ T cells, suggesting that host B cells play a role in maintaining pathological CD8+ T-cell responses. Imbalances in B-cell homeostasis could be used to identify patients a priori with a higher chance of response to rituximab treatment (Eudra-CT 2008-004125-42).